Circulatory Support with Venoarterial ECMO Unsuccessful in Aiding Endogenous Diltiazem Clearance after Overdose - Erin N. Frazee; Sarah J. Lee; Ejaaz A. Kalimullah; Heather A. Personett; Darlene R. Nelson (Case Reports in Critical Care)
Introduction. In cardiovascular collapse from diltiazem poisoning, extracorporeal membrane oxygenation (ECMO) may offer circulatory support sufficient to preserve endogenous hepatic drug clearance. Little is known about patient outcomes and diltiazem toxicokinetics in this setting. Case Report. A 36-year-old woman with a history of myocardial bridging syndrome presented with chest pain for which she self-medicated with 2.4 g of sustained release diltiazem over the course of 8 hours. Hemodynamics and mentation were satisfactory on presentation, but precipitously deteriorated after ICU transfer. She was given fluids, calcium, vasopressors, glucagon, high-dose insulin, and lipid emulsion. Due to circulatory collapse and multiorgan failure including ischemic hepatopathy, she underwent transvenous pacing and emergent initiation of venoarterial ECMO. The peak diltiazem level was 13150 ng/mL (normal 100–200 ng/mL) and it remained elevated at 6340 ng/mL at hour 90. Unfortunately, the patient developed multiple complications which resulted in her death on ICU day 9. Conclusion. This case describes the unsuccessful use of ECMO for diltiazem intoxication. Although past reports suggest that support with ECMO may facilitate endogenous diltiazem clearance, it may be dependent on preserved hepatic function at the time of cannulation, a factor not present in this case.